Studies on immunomodulatory effects of Salacia chinensis L. on albino rats - Sumalatha, Rama Bhat P., Shwetha R. Ballal and Sadananda Acharya (Journal of Applied Pharmaceutical Science)
India has a very rich diverse faunal and floral wealth spread across the length and breadth of country. Biodiversity hotspots like Himalayan region and Western Ghats are bestowed with innumerous number of potential medicinally important plants whose scientific research are yet to be taken up. Salacia chinensis is one among them and forms one of the known ethanobotanically used herbal drug for diabetes and aliments. A scientific study on physiological effect of Salacia chinensis can give baseline information about potency of plant drug formulae. Therefore this plant was taken up for the study of immunomodulatory effects on swiss albino rats. Rats were fed with a concentration of 1 mg/kg, 2 mg/kg, 4 mg/kg and 32 mg/kg body weight of aqoues extract of Salacia chinensis for a period of 14 days. Various hematological, serological and immunological parameters were studied at the end of 14days trial and compared with control group. Total leukocyte count, neutrophil percentage, blood glucose hemoglobin, hemagglutination antiboby titer against SRBC and delayed hypersensitivity reaction were found increased along the animals treated with 1mg/kg body weight of animal. On the contrary higher concentration of drug have reduced immune response compared to control group showing the negative effect of the higher concentration of drug on the immune response. The present study of Salacia chinensis evidently shows that concentration of 1mg/kg can boost the immune system and at the same time if used at higher concentration can determine the immune system.
Keywords: Hematological, Immunomodulatory, immune system, Salacia chinensis, Swiss albino rats.